Median and Ulnar Nerve Repair Using Sural Nerve Graft: A Case Report - Prasetyo, Eko; Oley, Maximillian C.; Manuhutu, Yovanka N.; Panduwinata, Dicky (e-CliniC, 2024)
Abstract: Most peripheral nerve injuries (PNI) are caused by trauma. Upper extrimities are most likely to get injured, and the radial nerve is the most common part in upper extrimites to be affected. There are different surgical options available to repair PNI. We reported a 48-years-old male consulted to the Neurosurgery Department for right upper limb weakness and numbness. He had history of laceration due to iron sheeting in the right arm. There was an irregular scar, weakness on right lower arm with hypesthesia, but no neurovascular distal (NVD) abnormalities were found. Further examination showed claw hand. EMG examination revealed total lesion of the right median and ulnar nerve, partial lesion of the right radial nerve with the lesion at wrist level, possibly neurotmesis according to Seddon Classification. Initial debridement, suturing, and repairing of radial artery and flexor carpi ulnar tendon were performed. The patient was then diagnosed as total lesion of the right median and ulnar nerve, partial lesion of the right radial nerve, post repair right ulnar and radial artery and flexor carpi ulnar tendon repair with the planning of nerve graft with no complication under monitoring. The patient was scheduled for sural nerve graft procedure. Early nerve repair or reconstruction is needed even though it only results in incomplete recovery for months to years. The sural nerve is great either in diameter or length which can be a huge source for the grafting of nerve and revealed good outcomes. Recent study showed incomplete recovery especially seen when the patient could not fully clench his hand and his thumb did not move properly during the movement. In conclusion, sural nerve graft is an appropriate choice for peripheral nerve injuries with more benefits included. Prognosis depends on how early the treatment performed and how severe the lesion is. Keywords: median nerve; sural nerve; peripheral nerve injury; nerve repair; nerve grafting